Social Commerce: Analysis of Influence Factors Customer Experience Management on Purchase Decision - Intan Bereani Wiguna; Gunawan Wang (Institute of Computer Science (IOCS), 2021)
The Internet is a technological breakthrough that disrupts many sectors around the world. The rapidly growing technology and internet in the business world gave rise to the term e-commerce. The use of the internet in social media increases online shopping transactions which in turn gives rise to a new term, namely social commerce. A social commerce strategy for managing experiences in designing and reacting to customer interactions with the aim of meeting or exceeding customer expectations is called Customer Experience Management (CXM). Where is the purchase decision that measures the decision-making process and consumer purchasing activities in social commerce. The purpose of this study is to examine and analyze the CXM factors that influence purchasing decisions in social commerce by using an empirical test that begins with a literature study and a questionnaire. Questionnaires were distributed to social commerce users using Google Forms. The data that has been collected will be processed using SmartPLS with validity, reliability, and regression tests. The results show that CXM factors that influence purchasing decisions in social commerce are reciprocity, consistency, transparency, and engagement, and CXM is able to convince entrepreneurs to develop business strategies that focus on improving consumer purchasing decisions and business profits.